Imam al-Qaradawi’s Moderate Approach on Non-Legislative Sunnah: Scholarly Debate and Contemporary Relevance. - Mahmudul Hasan, Syed (International Journal of Global Community, 2026)
This article explores Imam al-Qaradawi’s moderate hermeneutical interpretation of Non-Legislative Sunnah, as it has become the most contested issue in modern Islamic thought. After tracing the textual foundations and classical roots of the discussion, the paper surveys the voices of both modernists and traditionalists, along with their theological, methodological, and functional grounds. The study argues that Imam al-Qaradawi proposed a balanced methodology to reconcile the conflicting positions between excessive rationalism, which relativizes the legal bindingness of the Sunnah, and literal traditionalism, which absolutizes its authority. To clarify the position, it explains his epistemological foundation, core principles for distinguishing between the prophet’s multiple roles, and a mediating framework that harmonizes the sanctity of revelation with the flexibility and dynamism of Islamic law. The analysis demonstrates that his moderate framework aligns the Sunnah with the higher objectives of Islamic law- wisdom, justice, compassion, and public welfare- thereby enhancing its applicability in the modern era. The research further highlights his address to counter secular claims of the Sunnah’s obsolescence, clarifying its context-sensitive components that enhance its adaptability. Overall, the findings suggest that al-Qaradawi’s model lays the groundwork for a dynamic form of modern ijtihad, facilitating constructive Muslim engagement with contemporary legal, scientific, ethical, and governance challenges.